Allopregnanolone induces a diurnally dependent hyperphagic effect and alters feeding latency and duration in male Wistar rats. (17th April 2013) - Holmberg, E.; Bäckström, T.; Johansson, M.; Löfgren, M.; Haage, D.
Abstract Aim Gamma‐aminobutyric acid (GABA)‐ergic transmission from the hypothalamus is essential for normal feeding regulation, and hyperphagia can be induced by local application of GABAA‐receptor agonists to different feeding‐associated brain areas. The food intake in rats varies diurnally and that may influence the effect of GABAA‐receptor active compounds. The progesterone metabolite allopregnanolone is a highly potent endogenous positive modulator of the GABAA receptor. Therefore, it is easy to envisage that allopregnanolone would have a hyperphagic effect, but earlier reports in rat have given ambiguous results. However, a contributing factor for the discrepancy may be the time point of the diurnal cycle in which the experiments were performed. The aim of this study was to investigate the effect of allopregnanolone on intake of standard chow in male Wistar rats at different time points of the day. Methods Chow intake was measured after acute administration of allopregnanolone, and feeding behaviour was analysed to detect meal patterns. Results We found that allopregnanolone increased chow intake by up to four times in the dark part of the 24‐h cycle. The rats ate significantly more, and the effect of allopregnanolone was more prominent in the active (dark) compared with the inactive (light) period. Allopregnanolone also reduced feeding latency and prolonged the meal duration compared with vehicle. Conclusion Allopregnanolone seems to act at several levels of feeding regulation, that is, to initiate feeding and to prolong the duration of a meal, thereby increasing the meal size, especially in the dark period of the 24‐h cycle.